Pengaruh Senam Lansia Terhadap Kebugaran Lansia Di Posyandu Lanjut Usia Tegalsari Dan Posyandu Lanjut Usia Lodalang Siswodipuran Boyolali - Nur Ichsanna, Yustika, Dwi Rosella Komala Sari, SSt.FT.,M.Fis (2017)
The fit of elderly is one of indicator to use for determine of elderly healthlty. Gymnastics elderly is one excerise can do as routinely in oder to get fit. The objective this study is to know an effect of gymnastics elderly to fit of elderly between tegalsari posyandu and posyandu Lodalang Siswodipuran of Boyolali. The research is a quasi experiment, with pre test - post test with control group design. The sample were elderly count 20 elderly form posyandu tegalsari as treatment group and 10 elderly from the posyandu elderly lodalang as control group. The measurement of elderly fit use 6 minutes walking test and measured vo2max of elderly. analysis data use wilcoxon and Mann whitney test. The results of research of treatment group that average fit of pre test was 23.23 and post test was 25.84 . results Wilcoxon test obtained p = 0,000. Fit of Pre test control group was 22.84 and post test was 23.64. Results Wilcoxon test obtained p = 0,285 . The results of difference of effect of elderly Gymnastics to fit got p = 0,044. Conclusion their was an effect of gymnastics elderly to fit of treatment group. their was no an different from pre test post test of fit of control group. There was a different effect of gymnastics elderly to fit of elderly between tegalsari posyandu and posyandu Lodalang Siswodipuran Of Boyolali. Keyword: fit, gymnastics, elderly.